Implementasi Adaptasi Teknologi di Sekolah Sebagai Wujud Merdeka Belajar Melalui Media Pembelajaran Padlet - Enok Nurhasanah; Purwati Yuni Rahayu; Kusworo Kusworo (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
The achievement of effective learning depends on three things, namely input, process, and output. The qualifications of students with good abilities are certainly highly expected by the school for the achievement of educational goals. However, it cannot be denied that in reality the various abilities and characteristics of students make the school, especially teachers, able to innovate and adapt to all developments in the world of education today. Innovation in learning can be done in several ways such as updating or modifying learning models, using various learning resources, improvising teaching methods or methods, as well as learning media that are relevant to the current needs of students. These things must always be updated and adapted to the current changing paradigm of education. One of the efforts to improve the quality of learning today is to adapt technology. Based on this background, the Community Service this time has the theme "Implementation of Technology Adaptation in Schools as a Form of Independent Learning Through Padlet Learning Media."Keywords: Media; Adaptation; Technology; Padlet